Ethical Considerations for Compulsory Childhood Vaccination in Malaysia - Asari, Khairun Nisaa; Yusof, Yuhanif; Halim, Rohizan (Global Academic Excellence, 2021)
Childhood vaccination is an important tool for controlling and eliminating life-threatening infectious diseases among infants, as they are most vulnerable due to their weaker immune system. Due to this, certain countries resorted in enforcing compulsory childhood vaccination laws. Yet despite the proven effectiveness of childhood vaccination, it is also outweighed by numerous ethical implications. This paper focuses on the discussion of ethical considerations surrounding compulsory childhood vaccination in Malaysia. Focusing on the topic of compulsory vaccination of children, this paper discusses ethical issues related to parental autonomy, medical paternalism, compulsory childhood vaccination, and related legal issues. For the purpose of this article, the vaccination law as implemented in the United States will be referred. At the end of this article, some recommendations are proposed in relation to the drafting of legal framework on compulsory childhood vaccination in Malaysia. This article employs a doctrinal analysis and secondary data from academic journals and online databases